Predictors of severe forms of rotaviral infection in children - K. D. Ermolenko; A. I. Konev; K. Yu. Ermolenko; Yu. V. Lobzin (Журнал инфектологии)
Rotavirus infection (RVI) is one of the most common childhood diseases. The study of predictors of severe forms of this disease is of undoubted interest.Aim. Based on the study of the characteristics of the premorbid background, life history and clinical and laboratory parameters, determine predictors of severe forms of RVI.Patients and methods. In the departments of intestinal infections and resuscitation and intensive care of Pediatric Research and Clinical Center for Infectious Diseases in the period 2018 – 202. a retrospective study of 962 children aged 2 months to 2 years with rotavirus infection was carried out. he severity of the condition was assessed using the Clarke scale. To identify the most significant predictors of the development of severe forms of RVI, two groups of patients were compared: severe (> 16 points) and moderate (≤16 points) forms of RVI. Comparison of the frequency of occurrence of signs in the groups was performed using the Pearson χ2 test and Fisher’s exact method. The forecasting model was developed using discriminant analysis of the statistical package Statistica for Windows.Results. Severe forms of RVI were detected in 65 children. Among the patients with severe forms of RVI, there were no patients with completed preventive vaccination. Patients with severe forms of RVI were admitted to the hospital in the late stages of the disease and had a higher score on the CDS scale. Based on the research carried out, a model for predicting severe forms of RVI was developed. The features included in the model were: the day of illness at admission, the patient’s age, prehospital prescription of antibacterial drugs, the absence of completed vaccination against RVI, and the severity of dehydration. Assessment of the quality of the created model showed that the classification ability was 97.7%.Conclusion. Predictors of severe forms of RVI include admission to a hospital in the late stages of the disease with severe dehydration, early age, prehospital antibiotics and forced transfer to artificial feeding, and absence of completed prophylactic vaccination.